2023
DOI: 10.1002/mnfr.202200615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dβ‐Hydroxybutyrate‐(R)‐1,3 Butanediol on Appetite Regulation in People with Prediabetes

Abstract: Scope The main aim of the present study is to study the effect of acute ketosis on parameters of appetite regulation in prediabetes. Methods and results This is a randomized controlled trial registered under ClinicalTrials.gov identifier NCT03889210. After an overnight fast, 18 adults with prediabetes are assigned to consume a ketone monoester (d‐β‐hydroxybutyrate‐(R)‐1,3 butanediol) drink and a placebo drink in cross‐over fashion. Blood samples are collected every 30 min, from baseline to 150 min. Paired t te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The utility that exogenous ketone supplements may have during weight loss interventions is likely based on their ability to reduce stress markers during exercise and prolong the period of intense activity rather than modulate appetite [ 26 , 27 ]. This is further confirmed by an earlier CETUS study that reported no statistically significant changes in the appetite hormones ghrelin and peptide YY and no statistically significant differences in hunger when comparing the KEBHB group and the placebo group [ 29 ]. Prior to that study, there was a discrepancy in the literature about whether hunger is reduced during acute nutritional ketosis [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The utility that exogenous ketone supplements may have during weight loss interventions is likely based on their ability to reduce stress markers during exercise and prolong the period of intense activity rather than modulate appetite [ 26 , 27 ]. This is further confirmed by an earlier CETUS study that reported no statistically significant changes in the appetite hormones ghrelin and peptide YY and no statistically significant differences in hunger when comparing the KEBHB group and the placebo group [ 29 ]. Prior to that study, there was a discrepancy in the literature about whether hunger is reduced during acute nutritional ketosis [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 76%
“…This is further confirmed by an earlier CETUS study that reported no statistically significant changes in the appetite hormones ghrelin and peptide YY and no statistically significant differences in hunger when comparing the KEBHB group and the placebo group [ 29 ]. Prior to that study, there was a discrepancy in the literature about whether hunger is reduced during acute nutritional ketosis [ 29 , 30 , 31 ]. The earlier studies that reported on significant changes in appetite after ketone supplement consumption included controls that were isocaloric dextrose solutions and, therefore, contained carbohydrates (unlike the placebo used in the CETUS project) [ 29 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is in line with another CETUS study that showed that both hunger and hormones responsible for appetite regulation (e.g., ghrelin, peptide YY) were not significantly changed during acute ketosis. 39 Given that WAT has distinct metabolic properties based on where and how much of the tissue is deposited in the body 40 and taking into account that the secretomes of visceral fat and subcutaneous fat are distinct, 41,42 we investigated whether the effects of acute nutritional ketosis on asprosin and leptin are influenced by fat phenotypes. We found that leptin levels were not influenced by the VFV/SFV ratio, IHFD, and IPFD.…”
Section: Food and Function Papermentioning
confidence: 99%